Optimasi Penambahan Arang Sekam Padi pada Keramik Zeolit Berpori terhadap Sifat Fisik, Permeabilitas, dan Efektivitas Penyaringan Air - Safrudin Achmad Zailani; Sri Mulyo Bondan Respati; Muhammad Dzulfikar (Universitas Wahid Hasyim, 2026)
Water is an essential component of life; humans use it for various needs such as consumption, hygiene, and other domestic activities. However, water quality is increasingly threatened by pollution from industrial and domestic waste that is discharged without treatment, potentially containing heavy metals and hazardous substances. Therefore, there is a need for filtration technology that is economical, effective, and environmentally friendly. One promising alternative is the use of ceramic membranes, which exhibit high resistance to temperature, corrosion, and chemical contaminants. In this study, ceramic membranes were fabricated using natural zeolite as the base material combined with rice husk charcoal as a pore-forming agent. The variations in rice husk charcoal composition used were 0; 2.5; 5; 7.5; and 10 grams. The materials were sieved using 80-mesh and 120-mesh screens, with the fraction not passing the 120-mesh screen used as the main material. Testing was conducted using well water from the vicinity of Wahid Hasyim University in Semarang, with an initial TDS value of 521 ppm. After the filtration process, the best TDS value decreased to 106 ppm. The parameters analyzed included mass loss, volume loss, density (bulk and Archimedes), porosity, and water flow rate. The results showed that an increase in rice husk charcoal content caused an increase in mass loss and porosity, but decreased density and volume loss. Additionally, increased porosity contributed to an increase in the flow rate.